Numerical methods - Vedamurthy, V.N.; Iyngar, N.Ch.S.N (New Delhi : Vikas Publishing House, 1998)
Mathematics and Statistics
Keywords: Numerical methods; Emperical laws; Curve fitting; Equation theory; Algebric and transecendental equations; Linear equations; Difference equations